FLOUTING MAXIM ON FOOTBALL PLAYERS UTTERANCES IN DUBAI EYE 103.8 SPORT PODCAST - Ilham, Muhammad; Suswanto, Deni; Fauzi, Muhammad Erfan; Nurulaen, Yuyun (CALL, 2024)
This study explored the phenomenon of maxim flouting in the utterances of John Terry and Ashley Cole during the Dubai Eye 103.8 Sports Podcast. It tried to describe flouting maxims by John Terry in the podcast and the similarities and differences between the flouting maxim in the utterances of John Terry and Ashley Cole. A descriptive qualitative approach was employed to analyze and interpret the data, utilizing Grice's (1975) theory of conversational maxims as the theoretical framework to explain instances of maxim flouting in the cooperative principle observed in the speakers' utterances. Data collection was conducted through document analysis. The findings revealed that John Terry's utterances contained several instances of maxim flouting: 25 occurrences of flouting the maxim of quantity (64.8%), 1 instance of flouting the maxim of quality (3.7%), 8 instances of flouting the maxim of relation (20.7%), and 4 instances of flouting the maxim of manner (10.8%). In contrast, Ashley Cole's utterances included 21 occurrences of flouting the maxim of quantity (80.7%), 2 instances each of flouting the maxims of quality and relation (7.7% each), and 1 instance of flouting the maxim of manner (3.9%). The study also identified a key similarity: both speakers predominantly flouted the maxim of quantity in their utterances. However, a notable difference was observed in the frequency and distribution of the flouted maxims between the two speakers. Keyword: flouting maxim, cooperative principle, podcast, pragmatics